Association Between Body Mass Index and Morbidity and Mortality During Hospitalization After Trauma. Issue 2 (March 2022) - Soliman, Sara S.; Durling-Grover, Renay; Bilaniuk, Jaroslaw W.; Kong, Karen; Renna, Lauren; Hakakian, Daniel; Rolandelli, Rolando H.; Antonioli, Luca; Nemeth, Zoltan H.
Abstract : BACKGROUND: Literature suggests that unhealthy body mass index is a risk factor for adverse clinical outcomes. OBJECTIVES: To study the association between unhealthy body mass index and morbidity and mortality after trauma using the 2016 American College of Surgeons Trauma Quality Improvement Program database. METHODS: A retrospective review was conducted comparing the normal weight control group to the underweight, overweight, obese, severely obese, and morbidly obese groups for differences in demographic factors, injury severity score, comorbidities, length of stay, and complications. RESULTS: Underweight, overweight, obese, severely obese, and morbidly obese body mass indexes, in comparison to normal weight body mass index, were associated with a higher probability of developing at least one complication after trauma. Additionally, we observed a J-shaped curve when analyzing body mass index and mortality, suggesting that both high and low body mass indexes are positively associated with mortality. In fact, morbidly obese patients had the highest mortality rate, followed by underweight patients ( p < .001). Interestingly, however, multivariate logistic regression demonstrated that, compared with normal weight body mass index, overweight and obese body mass indexes were independently associated with 9.6% and 10.5% lower odds of mortality, respectively ( p < .001 and p = .001). CONCLUSION: Irrespective of preexisting comorbidities, injury severity score, and mechanism of injury, underweight, overweight, obese, severely obese, and morbidly obese body mass indexes were independently associated with higher risks of morbidity, whereas overweight and obese body mass indexes were associated with lower mortality risks. These findings emphasize the complex relationship between body mass index and clinical outcomes for trauma patients.